Urgent need of one health approach to contain antimicrobial resistance - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Muller Journal of Medical Sciences and Research, 2019)
The emergence of antimicrobial resistance has been regarded as a global public health concern and is expected to play an important role in the accomplishment of Sustainable Development Goals. It is quite alarming that resistance has been reported across the globe and we are reaching that stage in which common infections will become intractable. Acknowledging all these aspects, it is quite certain that we all don't have much time and there is an immense need to formulate a plan, implement holistic strategies and supplement the same with adequate financial support to minimize the impact on the future generations. It is quite obvious that these measures cannot be sustainable unless there is a strong political leadership and cooperation from all the sectors. In conclusion, antimicrobial resistance is a global concern and is a complex challenge to deal with. Thus, it is the need of the hour to formulate a One Health response to benefit the current and future generations of people.